Analisis Variasi Bahasa dalam Film Surga yang Tak Dirindukan 2 - Slama Slama; Rifatus Surur; Irfani Husnawiyah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
The diverse social backgrounds of characters in films often influence language use in communication, thereby reflecting the social conditions of the community. This study aims to describe the forms of language variation, forms of social stratification, and the relationship between language variation and social stratification in the dialogue of the film Surga yang Tak Dirindukan 2. A qualitative method with a descriptive-narrative approach was employed. Data collection involved a "listen-and-note" technique, requiring repeated listening to the film's dialogue and the recording of utterances containing language variations. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that the forms of language variation identified include geographical dialects, social dialects, and registers. Geographical dialects are evidenced by the use of Malay, the Betawi dialect, and Hungarian, while social dialects are observed through language usage influenced by the characters' professions, education, and social standing. Registers are identified through the use of medical and religious terminology as well as foreign languages. Social stratification within the film is demonstrated through differences in the characters' professions, education levels, social environments, and social status. The findings reveal a close relationship between language variation and social stratification, as language use is influenced by the speakers' social status, profession, education, and social environment.